Social networks and web 2.0 in 2009 - Margaix-Arnal, Didac (Anuario ThinkEPI, 2010)
This review of the situation of social networks and web 2.0 applications in libraries and information units in 2009 includes brief definitions of these concepts and a brief exploration of what may happen in 2010. Analysis of 2.0 technologies in libraries and in their environment, both in the organizations and the Spanish society in general, is based on various studies. Major changes during 2009 that can determine the movements of social networking services over the next year are described.
Keywords: Social networks; Web 2.0; Social web; Libraries; Library 2.0.